Improving the Quality of Care in a Central Emergency Department in Germany: A Best Practice Approach to Stakeholder-Oriented Process Optimization for the Continuous Improvement of Quality of Care and Patient Satisfaction with a Special Focus on the Implementation of a Structured Pain Management System...5th Annual Worldwide Nursing Conference (WNC2017), 24th–25th July 2017, Singapore. - Patrick Ristau, B. A.; Pfeuffer, Stephanie (Annual Worldwide Nursing Conference, 2017)
The Emergency Departments of German hospitals have faced a steadily increasing number of patients for several years as well as growing patients' expectations regarding hospital services. While pain is the main reason for patients to visit a hospital's emergency department (ED), it is a hardly explored phenomenon in this context. Moreover, while effective pain management is the most important dimension of patient satisfaction in EDs, there is a lack of studies in Central Europe which can be used for optimizing the deficient pain management in these units. This study will clarify whether the implementation of an interdisciplinary structured pain management improves the care of patients in the emergency room and whether its use improves patient satisfaction. Additionally, it investigates whether the implementation of such a structured pain management system will also bring advantages for the work of personnel employed in the emergency room. To this end, a multimethod approach was chosen, in which both the patients treated in the emergency room and the staff working there were interviewed by a written survey during a two-week examination period before and after the implementation. Included were all patients of the somatic departments who met the ethical criteria, as well as all doctors and nurses. Data analysis and processing was carried out using Microsoft Excel. It was found that the use of a structured pain management system leads to better, more effective pain treatment of the patients in the emergency department and increases their overall satisfaction with their treatment. Furthermore, it is easy to use by the staff and reduces their workload so that they have more time to spend on patient care.